Hubungan Faktor Pendukung Customer Relationship Manajemen dengan Loyalitas Pasien Poli Interna Ratulangi Medical Centre - Burhanuddin, Nurfardiansyah; Suyuti, Sartika (Window of Health : Jurnal Kesehatan, 2020)
Customer Relationship Management aims to process adaptation between clinics and customers. So any clinic is actually responsible for running a Customer Relationship Management program, every division, every clinic and every service worker must know about the program, its goals, and most importantly what their role is and how they can contribute to running the program. Based on the description above, it is necessary to conduct research aimed at identifying the Relationship between Supporting Factors of Customer Relationship Management (CRM) and Patient Loyalty at the Ratulangi Medical Center (RMC) Clinic in Makassar City. This research is a quantitative study using analytical surveys with a cross-sectional study design that is a research design that studies the relationship between independent variables (service clerks, service processes, service technology) and the dependent variable (patient loyalty). The population of this study was a visit of patients at the Ratulangi Medical Center (RMC) internal poly clinic in Makassar City who used health services in 2017, namely 1296 patients with a sample of 117 patients. The method of collecting samples is done by random sampling. Based on the results of the statistical test, the value of each service worker is p = 0.559, the service process p = 0.740, and service technology p = 0.760. All variables are not related to Customer Relationship Management (CRM) factors with patient loyalty at the Ratulangi Medical Center (RMC) internal poly clinic. This can be seen by the decision of the patient's loyalty level, most of which looked at the aspect of the service staff owned by the Ratulangi Medical Center (RMC) clinic. Regarding service officers, most of the patients agreed that the officers were able to provide the ability, skills and friendliness to patients at the Ratulangi Medical Center (RMC) Clinic. The service process for most patients agrees that the service process is easy to do. Helping officers to better recognize and establish close relationships with patients. The process dimension is formed due to the identification of profiles, communication with customers, and handling patient complaints at the Ratulangi Medical Center (RMC) Clinic. Service technology, some patients agree that easy service technology to obtain information, helps accelerate and optimize human factors and business processes in relationship management activities with patients at the Ratulangi Medical Center (RMC) Clinic. The conclusion of the study is that there is no relationship between the supporting factors of Customer Relationship Management (service personnel, service processes, and service technology) and patient loyalty at the Ratulangi Medical Center (RMC) clinic in Makassar in 2018.